1992
DOI: 10.1118/1.596758
|View full text |Cite
|
Sign up to set email alerts
|

Skin dose measurements for head and neck radiotherapy

Abstract: The use of immobilization plastic masks in head and neck radiotherapy can partially eliminate skin benefits derived from the utilization of megavoltage photon beams. Filters and blocks between the patient and the accelerator can further increase the skin dose value. In this study, the increase in surface dose due to 2 and 3.2 mm of plastic material utilized for patient immobilization was measured. Then, the effect of blocking trays, wedges, and blocks on skin dose in typical conditions for head and neck irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…Surface dose increases of 14% to 40% on phantoms under 2 mm of thermoplastic material with 6-MV photons have been reported (18)(19)(20)(21). Lee et al (22) showed that head-and-neck IMRT is not immune to this effect because both conventional and IMRT plans had a mean surface dose increase of 18% for 3-mm thermoplastic masks, an increase sufficient to cause substantial skin reactions.…”
Section: Introductionmentioning
confidence: 97%
“…Surface dose increases of 14% to 40% on phantoms under 2 mm of thermoplastic material with 6-MV photons have been reported (18)(19)(20)(21). Lee et al (22) showed that head-and-neck IMRT is not immune to this effect because both conventional and IMRT plans had a mean surface dose increase of 18% for 3-mm thermoplastic masks, an increase sufficient to cause substantial skin reactions.…”
Section: Introductionmentioning
confidence: 97%
“…Ayrıca bu maskelerin yüksek enerjili foton demetlerinin sahip olduğu cilt koruyucu (skin sparing) etkiyi azaltması, radyoterapide dikkat edilmesi gereken önemli bir konu olarak literatürde birçok çalışmacı tarafından araştırılmıştır. [1,3,5,6] Tedavi planlama sistemleri, yüzey dozunu doğ-ru olarak hesaplamada yetersizdir. [7] Yüzey ve build-up bölgesinde dozun doğru olarak ölçümü, tedavi planlama sistemi için kullanılan hesaplama algoritmalarının geçerliliği için gereklidir.…”
unclassified
“…3 ' 4 ' 7 The beam enters the extrapolation chamber through a thin foil coated to form the upper electrode (Fig. 1).…”
Section: Background Of Reviewmentioning
confidence: 99%